Analisis Syair Al-I’tiraf Karya Abu Nawas : Kajian Ilmu Ma’ani: Kajian Ilmu Ma’ani - Nuriyah, Afrizatun (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the poem Al-I'tiraf by Abu Nawas through the perspective of Ma'ani, a branch of Balaghah in Arabic literature. The poem was selected for its richness in rhetoric and linguistic beauty, reflecting themes of repentance and hope for Allah’s forgiveness. A qualitative-descriptive approach was employed with textual analysis to explore sentence structure, word choice, and rhetorical techniques such as ijaz, ithnab, and taqdim wa ta'khir. The findings reveal that Abu Nawas effectively integrated aesthetic elements with communicative effectiveness to convey moral and spiritual messages through eloquent and meaningful language. The rhetorical techniques employed emphasize themes of confession and hope, balancing emotional and intellectual aspects within the poem. This research contributes to understanding the richness of language and message delivery in classical Arabic literature, while paving the way for broader interdisciplinary studies.